Clinical outcomes after intravesical bacillus Calmette–Guérin for the highest‐risk non‐muscle‐invasive bladder cancer newly defined in the Japanese Urological Association Guidelines 2019. (18th March 2021) - Miyamoto, Tatsuki; Miyake, Makito; Toyoshima, Yuta; Fujii, Tomomi; Shimada, Keiji; Nishimura, Nobutaka; Iida, Kota; Nakahama, Tomonori; Hori, Shunta; Gotoh, Daisuke; Nakai, Yasushi; Torimoto, Kazumasa; et al.
Abstract : Objective: To assess the clinical outcomes of highest‐risk non‐muscle‐invasive bladder cancer patients treated with intravesical bacillus Calmette–Guérin. Methods: The medical charts of patients with non‐muscle‐invasive bladder cancer treated with intravesical bacillus Calmette–Guérin between 2000 and 2018 at a single institution were retrospectively reviewed. Patients were stratified into three groups (intermediate‐, high‐ and highest‐risk groups) according to the risk classification of the updated Japanese Urological Association guidelines 2019. Among the three groups, the intravesical recurrence‐free survival and progression‐free survival were estimated and compared, respectively. Furthermore, the different types of risk factors in the highest‐risk group were analyzed. Results: Of the 165 patients, 49 (30%) patients had intravesical recurrence and 23 (14%) patients showed progression to muscle‐invasive disease during a median follow‐up period of 53 months. Significant differences were not noted in the recurrence‐free survival and progression‐free survival among the three groups. Multivariable survival analysis of 74 patients in the highest‐risk group showed that carcinoma in situ in the prostatic urethra was a significant predictor associated with recurrence (hazard ratio 3.20, P = 0.026) and progression (hazard ratio 4.36, P = 0.013). Conclusions: Intravesical bacillus Calmette–Guérin can control highest‐risk non‐muscle‐invasive bladder cancer in most patients. Our findings might aid in decision‐making regarding the treatment of this subset of patients who require intensive treatment, such as intravesical therapy with bacillus Calmette–Guérin and radical cystectomy.